CXCL7-induced macrophage infiltration in lung tumor is independent of CXCR2 expression. Issue 2 (October 2015) - Unver, Nese; Esendagli, Gunes; Yilmaz, Guldal; Guc, Dicle
Highlights Macrophage infiltration was increased in CXCL7-overexpressing LLC tumors. Increased macrophage infiltration was independent of CXC receptor 2 (CXCR2). The overexpression of the CXCL7 chemokine induced M2-type macrophage infiltration. Accelerated tumor growth was detected in CXCL7-overexpressing tumors. The infiltration of T-cell subsets did not change in CXCL7-LLC tumors.